Apigenin induces DNA damage through the PKCδ-dependent activation of ATM and H2AX causing down-regulation of genes involved in cell cycle control and DNA repair - Arango, Daniel (2012)
Apigenin, an abundant plant flavonoid, exhibits anti-proliferative and anti-carcinogenic activities through mechanisms yet not fully defined. In the present study, we show that the treatment of leukemia cells with apigenin resulted in the induction of DNA damage preceding the activation of the apoptotic program. Apigenin-induced DNA damage was mediated by p38 and protein kinase C-delta (PKCδ), yet was independent of reactive oxygen species or caspase activity. Treatment of monocytic leukemia cells with apigenin induced the phosphorylation of the ataxia-telangiectasia mutated (ATM) kinase and histone H2AX, two key regulators of the DNA damage response, without affecting the ataxia-telangiectasia mutated and Rad-3-related (ATR) kinase. Silencing and pharmacological inhibition of PKCδ abrogated ATM and H2AX phosphorylation, whereas inhibition of p38 reduced H2AX phosphorylation independently of ATM. We established that apigenin delayed cell cycle progression at G1/S and increased the number of apoptotic cells. In addition, genome-wide mRNA analyses showed that apigenin-induced DNA damage led to down-regulation of genes involved in cell-cycle control and DNA repair. Taken together, the present results show that the PKCδ-dependent activation of ATM and H2AX define the signaling networks responsible for the regulation of DNA damage promoting genome-wide mRNA alterations that result in cell cycle arrest, hence contributing to the anti-carcinogenic activities of this flavonoid.